Association between the planetary health diet and sleep health in older adults: findings from a national community-based study - Ma, Xinyan; Zhao, Yuhong; Zhao, Hanqing; Zhou, Daan; Ai, Hao; Sun, Minghui (Frontiers in Nutrition, 2026)
BackgroundThe planetary health diet (PHD) has been established as linked to various diseases, yet its association with sleep health remains unexplored. This study is the first to investigate the associations of the PHD with sleep quality and duration, and to further evaluate its joint association with physical exercise, leveraging a national sample to inform healthy aging strategies.MethodsThis study utilized data from 9,041 elderly participants in the eighth wave of the Chinese longitudinal healthy longevity survey. A PHD Index (PHDI) was constructed based on 10 food groups from a simplified food frequency questionnaire, while sleep quality and duration data were obtained through face-to-face interviews. Multivariable logistic regression models were employed to examine the associations between the PHD and sleep quality and duration.ResultsThe study identified 4,730 (52.32%) participants with good sleep quality and 3,257 (36.02%) with adequate sleep duration. In the adjusted model, higher PHDI scores were associated with better sleep quality (OR = 1.35; 95% CI = 1.20–1.52) and adequate sleep duration (OR = 1.36; 95% CI = 1.20–1.54). Each one-point increase in the PHDI score was associated with 5 and 4% higher odds of good sleep quality and adequate sleep duration, respectively. Notably, in the joint analysis, participants with both a high PHDI and regular physical exercise exhibited significantly higher odds of good sleep quality (OR = 1.64; 95% CI: 1.42–1.89) and adequate sleep duration (OR = 1.48; 95% CI: 1.27–1.73) compared to those with a low PHDI and no exercise.ConclusionOur findings indicate that a higher PHD was associated with better sleep quality and adequate sleep duration, highlighting the dual benefits of plant-based and sustainable diets for personal sleep health and the planet.